PLACE OF THE PRINCIPLE OF GOOD FAITH IN THE SYSTEM OF PRINCIPLES OF ADMINISTRATIVE JUSTICE - Yatsuba, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the place of the principle of good faith in the system of administrative justice principles. The author notes that the problem of developing effective ways to protect the rights, freedoms and legitimate interests of a person and a citizen, as well as a legal entity, has become an urgent issue for Ukraine since its independence. Research methods: the chosen topic of scientific research requires the use of various scientific methods and approaches to obtain high-quality results. Therefore, the following research methods were used to solve the tasks set: analysis; systematic method; analytical method, etc. Results: considering the experience of Ukraine along with the experience of stable democracies, we can say that our country, in comparison, has passed a very short way of introducing and consolidating democratic traditions and values. Over the years of independence, significant steps have been taken in this direction. However, the problem of forming effective means and measures to protect rights, freedoms, and legitimate interests is still relevant for us. Of all the means and measures to protect the rights, freedoms, and legitimate interests of a person, the most effective and reliable today is the judicial method of protection. Discussion: the protection of human rights, the application of measures of state responsibility for the violation of such rights should not only be declarative constitutional norms, but should be duly guaranteed by appropriate means of public administration. In this aspect, the institution of administrative justice is one of the main guarantees of the implementation of the mechanism of the state’s responsibility to the individual. The functioning of administrative justice is a guarantee of preventing manifestations of bureaucratic arbitrariness and bureaucratic abuse of powers defined by law. And the level of ensuring the rights and freedoms of participants in public legal relations depends on how effective the system of administrative justice is.